Facilitation of Corticostriatal Transmission following Pharmacological Inhibition of Striatal Phosphodiesterase 10A: Role of Nitric Oxide-Soluble Guanylyl Cyclase-cGMP Signaling Pathways - Padovan-Neto, Fernando E. (J Neurosci, 2015)
The striatum contains a rich variety of cyclic nucleotide phosphodiesterases (PDEs), which play a critical role in the regulation of cAMP and cGMP signaling. The dual-substrate enzyme PDE10A is the most highly expressed PDE in striatal medium-sized spiny neurons (MSNs) with low micromolar affinity for both cyclic nucleotides. Previously, we have shown that systemic and local administration of the selective PDE10A inhibitor TP-10 potently increased the responsiveness of MSNs to cortical stimulation. However, the signaling mechanisms underlying PDE10A inhibitor-induced changes in corticostriatal transmission are only partially understood. The current studies assessed the respective roles of cAMP and cGMP in the above effects using soluble guanylyl cyclase (sGC) or adenylate cyclase (AC) specific inhibitors. Cortically evoked spike activity was monitored in urethane-anesthetized rats using in vivo extracellular recordings performed proximal to a microdialysis probe during local infusion of vehicle, the selective sGC inhibitor ODQ, or the selective AC inhibitor SQ 22536. Systemic administration of TP-10 (3.2 mg/kg) robustly increased cortically evoked spike activity in a manner that was blocked following intrastriatal infusion of ODQ (50 μm). The effects of TP-10 on evoked activity were due to accumulation of cGMP, rather than cAMP, as the AC inhibitor SQ was without effect. Consistent with these observations, studies in neuronal NO synthase (nNOS) knock-out (KO) mice confirmed that PDE10A operates downstream of nNOS to limit cGMP production and excitatory corticostriatal transmission. Thus, stimulation of PDE10A acts to attenuate corticostriatal transmission in a manner largely dependent on effects directed at the NO-sGC-cGMP signaling cascade.